Improving Purchase Intention Through Celebrity Endorsement, Social Media Advertising, and Customer Experience With Brand Image as a Moderation - Wibisana, Luqman Ikhsanudin; Miswanto, Miswanto; Gusmao, Maria Alda Saores (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the effect of celebrity endorsement, social media advertising, and customer experience on purchase intention, with brand image as moderation. This research focuses on a case study of the McD BTS Meal product, the result of a collaboration between the McDonald brand and the South Korean boyband, Bangtan Boys or BTS. Two hundred ten respondents filled out the questionnaire, but only 184 respondents were eligible to be processed for data testing. The respondents are in Indonesia. The data processing used the WarpPLS version 7 program, and the validity and reliability tests used the SPSS version 26 program. The research findings show the following. First, celebrity endorsement, social media advertising, and customer experience positively influence purchase intention. Second, brand image cannot moderate the influence of social media advertising and customer experience on purchase intention. Third, brand image moderates the effect of celebrity endorsement on purchase intention.